2021
DOI: 10.3390/agriculture11070609
|View full text |Cite
|
Sign up to set email alerts
|

Functional Quality of Improved Tomato Genotypes Grown in Open Field and in Plastic Tunnel under Organic Farming

Abstract: In response to urgent demand to raise awareness of the nutritional and health benefits of tomato consumption and to advocate for healthy diets through increased sustainable production and consumption of fruits and vegetables, this study is intended to promote a healthy and balanced lifestyle, sharing the best practices of production and consumption. The aim of this research was to compare the effects of the growing system (field vs. plastic tunnel) and of genotype characteristics for organic improved tomato ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 43 publications
4
11
0
Order By: Relevance
“…In this respect, fruits harvested from open field had significantly higher percentage of dry matter, vitamin C and total carbohydrates in both seasons than in those harvested from plastic house. These results are in accordance with those presented by Murariu et al (2021), who reported that the crop system had a major influence on vitamin C content and dry matter in tomato fruits, being recorded the highest value in the case of organic tomatoes from the field, with statistically significant differences compared to varieties cultivated in the plastic tunnel. The Whitley et al (2011) reported that changes in temperature from day to night influence metabolic rate, resulting in differential effects on carbohydrate metabolism and respiration.…”
Section: Effect Of Production Systems Cultivarssupporting
confidence: 93%
“…In this respect, fruits harvested from open field had significantly higher percentage of dry matter, vitamin C and total carbohydrates in both seasons than in those harvested from plastic house. These results are in accordance with those presented by Murariu et al (2021), who reported that the crop system had a major influence on vitamin C content and dry matter in tomato fruits, being recorded the highest value in the case of organic tomatoes from the field, with statistically significant differences compared to varieties cultivated in the plastic tunnel. The Whitley et al (2011) reported that changes in temperature from day to night influence metabolic rate, resulting in differential effects on carbohydrate metabolism and respiration.…”
Section: Effect Of Production Systems Cultivarssupporting
confidence: 93%
“…Carbohydrate content of the tomato fruit can be influenced by many factors, including environmental conditions and crop technology, method of assessing content, harvest period and genotypes [40][41][42][43][44]. The values for carbohydrates, based on glucose plus fructose levels in this experiment, demonstrate the strong influence of genotype and individual genetic heritage of cultivars on the potential to accumulate a certain amount of carbohydrates.…”
Section: Chemical Compounds Variations On Tomato Fruitsmentioning
confidence: 79%
“…Tomato fruits are rich in carotenoids (e.g. bcarotenoids and lycopene), ascorbic acid (vitamin C), tocopherol (vitamin E), and bioactive phenolic compounds such as quercetin, kaempferol, naringenin and lutein, caffeic, ferulic and chlorogenic acids (Dasgupta and Klein, 2014;Mihalache et al, 2020;Stoleru et al, 2020;Murariu et al, 2021). The carotenoids from tomatoes are known to display anticancer properties and to be excellent deactivators of reactive oxygen species (ROS) (e.g.…”
Section: Introductionmentioning
confidence: 99%